2011
DOI: 10.1073/pnas.1114372109
|View full text |Cite
|
Sign up to set email alerts
|

Disordered form of the scaffold protein IscU is the substrate for iron-sulfur cluster assembly on cysteine desulfurase

Abstract: The scaffold protein for iron-sulfur cluster assembly, apo-IscU, populates two interconverting conformational states, one disordered (D) and one structured (S) as revealed by extensive NMR assignments. At pH 8 and 25°C, approximately 70% of the protein is S, and the lifetimes of the states are 1.3 s (S) and 0.50 s (D). Zn (II) and Fe(II) each bind and stabilize structured (S-like) states. Single amino acid substitutions at conserved residues were found that shift the equilibrium toward either the S or the D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
169
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(181 citation statements)
references
References 38 publications
10
169
0
Order By: Relevance
“…The conformational transition of IscU has been mimicked and further characterized under various conditions. For example, the binding of Zn 2+ [77], Fe 2+ [101], or [2Fe–2S] [78] stabilizes the S-state (Figs. 5A, B).…”
Section: Recent Results From Our Laboratorymentioning
confidence: 99%
“…The conformational transition of IscU has been mimicked and further characterized under various conditions. For example, the binding of Zn 2+ [77], Fe 2+ [101], or [2Fe–2S] [78] stabilizes the S-state (Figs. 5A, B).…”
Section: Recent Results From Our Laboratorymentioning
confidence: 99%
“…Indeed, the high stability of cluster ligation on holoIscU when present as complex with HscB may minimize losses of cluster atoms when cluster transfer to nascent FeS apoprotein(s) is not immediately required. In the frame of the complicated interplay among proteins involved in FeS cluster biogenesis [37], it may be worth exploring also the possible effects of HscB-induced structural rigidity of apoIscU as for the interaction with those isc-encoded proteins that are involved in delivering cluster atoms, such as the IscS desulfurase [20,32,36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that IscU has evolved to exist in a disordered conformational state that is the initial substrate for the desulfurase and converts to a structured state that stabilizes the cluster once it is assembled. On these bases, it was concluded that the disordered form of IscU is the substrate for cysteine desulfurasemediated assembly of iron-sulfur clusters [20]. It has also been suggested that forms of IscU with different structural stability play alternate roles in their function as scaffolds during FeS biosynthesis [21].…”
Section: Introductionmentioning
confidence: 98%
“…The canonical mechanism for Fe-S cluster biogenesis involves the pyridoxal phosphate dependent enzyme cysteine desulfurase, L-cysteine as the source of sulfur, an iron delivery protein, a reductant (ferredoxin), and a scaffold protein [5,6]. We have shown that the human scaffold protein ISCU (like its Escherichia coli counterpart IscU [7]) populates two interconverting conformational states: one that is structured (S), and one that is dynamically disordered (D) [8]. Human cysteine desulfurase (NFS1) differs from that of E. coli (IscS) by the requirement for two accessory proteins: ISD11 and mitochondrial acyl carrier protein (ACP).…”
mentioning
confidence: 99%